Distorted trade barriers: A comment on "distorted gravity" - Matthew T. Cole (University College Dublin, UCD School of Economics, 2010)
Since firm heterogeneity has been introduced into international trade models, the importance of firm entry and exit (the extensive margin) has been highlighted. Thomas Chaney (2008) illustrates how accounting for heterogenous firms (and this extensive margin) alters the standard gravity equation. In particular, it reverses the previously predicted effect the elasticity of substitution has on the elasticity of trade flows. Further, Chaney shows that the elasticity of trade flows with respect to variable trade costs is a constant. As is common, iceberg transport costs are used as the variable trade barrier. However, in many empirical studies, ad valorem tariffs are also used as a form of trade barrier, which as Cole (2010) points out, is not isomorphic to iceberg transport cost in a monopolistically competitive setting. In this comment, I solve the Chaney (2008) model using ad valorem tariffs instead of iceberg transport costs and show the elasticity of trade flows with respect to tariffs is not constant, but depends on the elasticity of substitution.
hdl:10197/2653
Keywords: F10; F12; F17; 330; Intra-industry trade; Gravity; Firm heterogeneity; Monopolistic competition